School nutrition directors’ experiences and perceptions of expanding the school breakfast program in Kansas - Harris, Kyleen Darci (Kansas State University, 2020)
The School Breakfast Program (SBP) is a federally assisted meal program with the primary goal of providing a nutritious breakfast to children that arrive at school without adequate nourishment essential for learning. Kansas has nationally recognized Child Nutrition Programs; however, like many states, the SBP remains underutilized compared to the National School Lunch Program. Improving access to the SBP has the potential for positive student academic and health outcomes. Innovative breakfast delivery models that offer breakfast after the start of the school day, including grab-and-go, second chance breakfast, and breakfast in the classroom, have been demonstrated to effectively increase participation in the SBP. The purpose of this study was to explore innovative breakfast delivery models and the impacts of expanding the SBP in Kansas schools. The Diffusion of Innovation theory was used to guide focus group question development and data analysis. The sample included school nutrition directors (SNDs) representing public-school districts participating in the USDA-supported SBP and currently operating an innovative breakfast delivery model, for a minimum of the past school year. Qualitative data were collected from four synchronous online focus groups consisting of three to seven participants. The final sample size was 19 SNDs. Thematic analysis was conducted on each transcript to identify significant themes, frequencies, and patterns in responses. Key findings included themes related to the relative advantages over the traditional breakfast program, compatibility with district values and student needs, supportive social systems and communication channels, modifiability of the innovative breakfast models, impacts on students, and program sustainability. This study underscores the value of school administrator support and collaboration with stakeholders in the school environment when expanding the SBP. Innovative breakfast delivery models were commonly modified to meet the evolving needs of the schools and to improve program efficiency. Participants perceived their innovative breakfast delivery models as sustainable due to increased program participation, satisfaction, and revenue. Many school districts observed positive impacts on students, including fewer nurse visits and improved behaviors in schools. Expanding the SBP into the school day appears to have a positive impact on the school environment by improving student and staff relationships. These findings provide stakeholders with information and supporting evidence that can be used to improve the implementation of innovative breakfast delivery models to increase SBP participation.
Keywords: School Breakfast Program